High Resolution Infrared Spectroscopy in Astronomy: Proceedings of an ESO Workshop Held at Garching, Germany, 18-21 November 2003 - Käufl, Hans Ulrich; Moorwood, Alan F. M.; Siebenmorgen, Ralf (Springer Berlin Heidelberg, 2005)
Alan F. M. Moorwood
Keywords: Konferenzschrift -- 2003 -- Garching, München; Infrarotastronomie